PENGARUH DUKUNGAN SOSIAL KELUARGA TERHADAP PSIKOLOGIS WARGABINAAN PEMASYARAKATAN - Elsafira Maghfiroti Resyanta (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2020)
Correctional Institution is a place to carry out a formation for prisoners and correctional students. Based on data from the Directorate General of Prisons (Ditjenpas) as of March 2020 the number of prisoners in prison Class II Cibinong reached 1,465 people not all come from Cibinong and surrounding areas but also not a few who come from outside. This has become one of the factors of development to get support from the family. This research raised the issue of how the influence of family social support on the psychological of prisoners? This study aims to determine the effect of family social support on the behavior of prisoners. This research was conducted in Prison Class II Cibinong. This research used a quantitative approach research method. This research was conducted on March 2020. The data were obtained using questionnaire filling techniques. The process of taking research samples used the technique of Simple Random Sampling, which was a sampling method in which each individual has the opportunity to become a sample in research. After that, the data was collected by using questionnaire distribution techniques that have been prepared with the answer format on a Likert scale, in-depth interviews, and literature studies to obtain correct and detailed data and information. The results of this study indicate that family social support influences the behavior of prisoners. Inmates who get social support from their families will be more positive and have a calmer psychological.